2015
DOI: 10.1016/j.str.2015.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Mechanistic Insights into the Latrophilin3-FLRT3 Complex that Mediates Glutamatergic Synapse Development

Abstract: SUMMARY Latrophilins (LPHNs) are adhesion-like G protein coupled receptors implicated in attention-deficit/hyperactivity disorder (ADHD). Recently, LPHN3 was found to regulate excitatory synapse number through trans interactions with fibronectin leucine-rich repeat transmembrane 3 (FLRT3). By isothermal titration calorimetry, we determined that only the olfactomedin (OLF) domain of LPHN3 is necessary for FLRT3 association. By multi-crystal native-SAD phasing, we determined the crystal structure of the OLF doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 35 publications
(63 reference statements)
4
32
0
Order By: Relevance
“…Most protein–protein interactions shown for FLRT involve the LRR domain, which promotes cell adhesion via interaction with itself (homophilic) 2 or with Latrophilin 7 , and triggers cell repulsion by binding Unc5 receptors 1 4 5 . FLRT–FLRT and FLRT–Latrophilin interactions are mediated by overlapping binding sites on the concave face of the LRR 6 12 13 . Repulsive FLRT–Unc5 interactions are mediated via a distinct binding site at a lateral side of the FLRT LRR 5 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most protein–protein interactions shown for FLRT involve the LRR domain, which promotes cell adhesion via interaction with itself (homophilic) 2 or with Latrophilin 7 , and triggers cell repulsion by binding Unc5 receptors 1 4 5 . FLRT–FLRT and FLRT–Latrophilin interactions are mediated by overlapping binding sites on the concave face of the LRR 6 12 13 . Repulsive FLRT–Unc5 interactions are mediated via a distinct binding site at a lateral side of the FLRT LRR 5 .…”
mentioning
confidence: 99%
“…The interaction of these ligands with Latrophilin is best understood in the context of trans -cellular adhesion 7 28 30 . Using mutagenesis, we recently mapped the FLRT-binding site on the Latrophilin Olf domain 6 , which was further defined by recent structural analysis of dimers formed by FLRT3 LRR and Latrophilin3 Olf (refs 12 , 13 ). Interestingly, a cell-based binding assay suggested that Latrophilin, FLRT and Unc5 form a ternary complex 13 , although the structural arrangement of the ternary interaction remained elusive.…”
mentioning
confidence: 99%
“…ADGRL3, also known as LPHN3, is a member of the latrophilin subfamily of secretin G protein coupled receptors that is expressed in the striatum, a part of the brain important for motor control and reward [27]. ADGRL3 is known to play a role in glutamatergic synapse development [28]. Loss of function in a homolog, lphn3.1, leads to a hyperactive motor phenotype in developing zebrafish and in the ADGRL1 knock-out mouse [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…To date, the only other olfactomedin domain captured structurally in multiple configurations is latrophilin 3 (LPHN3), which harbors an Asn-Asp-Asp triad, which is coincidentally permuted in sequence compared with the myoc-OLF triad Asp-Asn-Asp. In the structure of mouse latrophilin 3 (MmLPHN3; PDB entry 4rml; Ranaivoson et al, 2015), the long top loop adopts an open conformation that is unique among all other OLF structures [ Supplementary Fig. S5(a)] and an Mg 2+ ion was found to be hexacoordinated to the equivalent of Asp478 [Asp436; Supplementary Fig.…”
Section: Myoc-olf N428e/d478kmentioning
confidence: 99%
“…High-resolution crystal structures of the $30 kDa fivebladed -propeller OLF domain are available for four subfamily members: olfactomedin-1 (Pronker et al, 2015;Hill et al, 2015), latrophilin (Lu et al, 2015;Ranaivoson et al, 2015;Jackson et al, 2016), myocilin (Donegan et al, 2015) and gliomedin (Han & Kursula, 2015;Hill et al, 2015). While the folds are nearly indistinguishable [ Fig.…”
Section: Introductionmentioning
confidence: 99%